Human rights in education implication schema based on the study of the UN Economic and Social Council’s 2030 agenda - Kurniawan, Agung Budi (Masyarakat, Kebudayaan dan Politik, 2024)
Human rights in education are an essential area that needs to be the highest priority for improving almost the entire world, especially for the 2030 agenda. This research analyzed the human rights in education values inside the UN Economic and Social Council’s declaration goal 4 of the official document entitled “Building back better from the coronavirus disease (COVID-19) while advancing the full implementation of the 2030 Agenda for Sustainable Development”. The data are analyzed through a critical discourse approach in qualitative design and discourse organization analysis method. There are nine main human rights in education found inside the declaration including ensuring and protecting education equality, education, and learning development acceleration, preparing and providing sufficient education funding, cultural diversity in education, providing a safe environment for physical and mental health, providing safe, modern and convenient infrastructure and teaching-learning facilities, gender equality in education, internet literacy in education, involving every country as to the world’s global meeting and cooperation of education. The focus of improvement on human rights in education is concluded to be dynamic, which is influenced by economic, welfare, politics, IT, and other integral aspects of development and depends on the world’s and a country’s needs and future desire.